MODERN APPROACHES TO THE TREATMENT OF PATIENTS WITH A COMBINATION OF ANKYLOSING SPONDYLITIS AND CROHN`S DISEASE - Kulchytska, O.M.; Kuzminova, N.V.; Lozinsky, S.E.; Knyazkova, I.I.; Kalinichenko, S.O.; Nazarova, M.S.; Burdeina, L.V. (World of Medicine and Biology, 2025)
Ankylosing spondylitis and Crohn's disease are chronic inflammatory conditions that impact both physical and psychological health. Ankylosing spondylitis primarily affects the spine, causing pain, inflammation, and stiffness, potentially leading to disability. Crohn's disease affects the gastrointestinal tract, causing inflammation, tissue damage, and complications such as stenosis and fistulas, with symptoms like abdominal pain and diarrhea. Although these diseases affect different areas, their inflammatory processes share similar mechanisms and often coexist in the same patient. Both conditions involve immune system dysregulation, leading to chronic systemic inflammation. Treatment aims to reduce symptoms, achieve remission, and prevent complications. However, therapy for comorbid Ankylosing spondylitis and Crohn's disease must be carefully planned, as drugs used for one condition, such as non-steroidal anti-inflammatory drugs for Ankylosing spondylitis, can worsen Crohn's disease. Biological agents targeting inflammatory mechanisms, such as tumor necrosis factor α inhibitors and interleukin blockers, have significantly improved treatment, though individual approaches are necessary due to varying effectiveness and side effects.
Keywords: ankylosing spondylitis; inflammatory bowel disease; Crohn's disease; ulcerative colitis